PENGARUH MEDIA DASAR MS DAN N TERHADAP PERKEMBANGAN EMBRIO 6 SOMATIK PADA KULTUR MERISTEM JAHE (Zingiber officinale Rosc.) - Otih Rostiana; Sitti Fatimah Syahid (Research Center for Biology-Indonesian Institute of Sciences, 2007)
This study was performed to evaluate the development of somatic embryo from embryogenic calli of ginger meristem culture. Completely randomized design was applied, replicated 4 times. Embryogenic calli from meristem tissue of inner shoot bud of rhizome obtained on MS medium containing 100 mg/L glutamine, 2% sucrose with the addition of 1.0 mg/L 2,4-D and 3.0 mg/L BA, were subjected to proliferation medium, MS and N basal media containing 3% mannitol. Then, transferred into somatic embryo maturation medium, either MS or N basal media supplemented with 6% sucrose. The number of somatic embryos-formed significantly affected by the proliferation medium applied. The highest number of somatic embryos (about 82.0 per 1 g friable calli) was achieved on the MS medium, 4 weeks after incubation. In addition, the optimum growth of embryogenic calli containing somatic embryos was obtained on MS and N medium supplemented with 6% sucrose. There were significantly difference between the media applied (MS and N ) to somatic embryos maturation. The highest number of mature somatic embryos (57.2 embrios) was achieved on the MS medium, 18 days after incubation.